2012
DOI: 10.1016/j.actaastro.2012.04.014
|View full text |Cite|
|
Sign up to set email alerts
|

Surgery in space: Where are we at now?

Abstract: In the coming decades, as we continue our path of space exploration beyond Earth's orbit, we will be required to provide sound medical and surgical care for the safety of space travellers and space flight participants. A few investigations have taken place in the field of surgery in space. In this paper, the authors review the present literature in order to identify possible limitations that currently exist and that could impair our ability to provide surgical care during spaceflight, from the pre-operative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Ultrasound results may be affected by fluid shifts but remains a helpful diagnostic tool . Studies have shown there is no significant difference in observed blood loss during simulated laparoscopies …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasound results may be affected by fluid shifts but remains a helpful diagnostic tool . Studies have shown there is no significant difference in observed blood loss during simulated laparoscopies …”
Section: Resultsmentioning
confidence: 99%
“…Blood collection in microgravity should be possible with the use of a vacuum, syringe, or pump. Infusion could be done with a pressure bag or a syringe …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the heightened risk of contamination is potentially bidirectional, as conventional surgical barriers may not be effective without gravity. In addition, fluids and organs behave differently in space than on Earth, interfering with surgical exposure and retraction (5). Finally, microgravity may result in impaired postoperative wound healing (6,7).…”
Section: Unfavorable Physical Environmentmentioning
confidence: 99%
“…This proved to provide adequate drainage and eliminated the risk of contamination from the vehicle environment. Another advantage was that the blood from a hemothorax in this type of system could be used to autotransfuse a trauma victim [44].…”
Section: Spacecraft Emergenciesmentioning
confidence: 99%